Forced migration in childhood: Are there long-term health effects?. (December 2016) - Saarela, Jan M.; Elo, Irma T.
Abstract: Studies on the health of migrants have increased considerably in number in recent years, but little is still known about the long-term health effects associated with forced migration, and particularly for people who were forced to migrate as children. Data shortcomings together with the methodological challenges of studying migrant populations limit the ability to disentangle the roles of various factors that influence migrant health outcomes. Finland provides an unusual opportunity to study long-term health consequences associated with forced migration. During World War II, twelve per cent of the Finnish population was forced to leave the region nowadays referred to as Ceded Karelia. After the war, these Karelians could not return home because the area was relinquished to the Soviet Union. Using high quality, linked register-based data for the period 1988–2012, we investigate whether this forced migration had long-term health consequences for those who were forced to migrate as children. Comparison groups are non-displaced persons born on the adjacent side of the new border, and people born elsewhere in Finland. Health at ages 43–65 years is measured by receipt of sickness benefit, which is an indicator of short-term illness, and receipt of disability pension, which reflects long-term illness or permanent disability. All-cause and cause-specific mortality is analysed at ages 43–84 years. We find no support for the hypothesis that the traumatic event of being forced to migrate during childhood has long-term negative health consequences. The forced child migrants have lower odds for receipt of sickness benefit, and women also have lower odds for receipt of disability pension. The mortality results are largely driven by patterns specific for eastern-born populations of Finland. A likely reason behind the absence of negative health consequences is that these migrants seem to have integrated well into post-war Finnish society. Highlights: Analyse long-term health effects associated with forced migration in childhood. A unique event that forced 12 percent of Finnish population to relocate during WWII. Circumvent common methodological challenges of studying migrant populations. Register-based data to analyse health and mortality from main causes in 1988–2012. Absence of health malicious effect likely due to successful integration.